Prevalence of strongyloidiasis in Southeast Asia: a systematic review - Mohd Shafik Abd Majid,; Fadzrul Hafiz Johani,; Wan Rosmawati Wan Ismail,; Diyana Mohd Mokhtar,; Qistina Mohd Ghazali,; Norfazilah Ahmad,; Mohammad Saffree Jeffree,; Mohd Rohaizat Hassan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Strongyloides stercoralis is an intestinal helminth that infects humans through contact with soil containing the larvae. Methods A systematic search was performed for relevant titles, abstract and keywords in database from Cochrane Library, PLOS One, PubMed and several other sources in October 2017 based on PICO strategy. Out of 511 papers that were evaluated for possible inclusion, final assessment for eligibility has yielded a total of 17 papers to be included which were found suitable for analysis covering period from 2012 till 2016. Results A major challenge of giving an overview of prevalence data for S. stercoralis lies in the low sensitivity of diagnostic method used which resulted in very low prevalence in certain countries. Cambodia and Laos presented with high prevalence ranging from 17.4% to 45.9% by using high sensitivity of diagnostic methods. The current prevalence situation of S. stercoralis in Southeast Asia still have wide gaps remains due to several reasons. Conclusions The information we have today only scratches the surface which cannot truly reflect the true burden of S. stercoralis in Southeast Asia The main risk factor is personal hygiene practices especially amongst males.